2011
DOI: 10.1177/0960327111405861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the impact of hospital types on the availability of antidotes for the management of acute toxic exposures and poisonings in Malaysia

Abstract: Most Malaysian government hospitals stocked some important antidotes. Raising awareness of the importance of antidotes by education, regular review of antidote storage, distribution plans, and appropriate legislation might provide solutions. Coordination between Malaysian hospitals and the National Poison Centre at Universiti Sains Malaysia is also important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
0
21
2
Order By: Relevance
“…Currently, there are no generally recognised specific criteria that define the preparedness of an ED for the management of acute toxic exposures and poisonings. A list of commonly required resources and items which might be used for the treatment of acute poisoning was compiled from the published recommendations [8,11,16,27-31]. …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no generally recognised specific criteria that define the preparedness of an ED for the management of acute toxic exposures and poisonings. A list of commonly required resources and items which might be used for the treatment of acute poisoning was compiled from the published recommendations [8,11,16,27-31]. …”
Section: Discussionmentioning
confidence: 99%
“…The distance between the general hospital and the district one is not more than 100 km. Each state has at least one general hospital, and is supported by district hospitals, polyclinics as well as rural clinics [17]. The General Hospitals are the biggest government hospitals in each state of Malaysia.…”
Section: Study Area and Sample Sizementioning
confidence: 99%
“…Although emergency supportive care is considered the foundation of toxicological emergency management, unintentional and intentional poisoning continue to be a major contributor to annual mortality rates worldwide [2]. Morbidity, mortality, and the length of hospitalization may be reduced by the appropriate and well-timed use of antidotes [3]. The mainstay in the proper management of a patient in need for an antidote is the immediate administration of the needed antidote and its availability in the hospital emergency.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the availability of antidotes globally is scarce, however recent studies have shown that antidotes are inadequately stocked in many countries and their availability also varies significantly among hospitals within the same country [36]. Accordingly, Dart et al, developed recommendations for antidote stocking and categorizing their availability according to the immediacy of their use in USA [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation